(untitled) - Maestri, George (Alameda, CA, 2005)
One look and you'll see this Maya book is different from all the others. It presents core Maya features visually, using pages that are packed with beautiful graphics and loaded with detailed explanations on every crucial feature of Maya's interface. Engaging step-by-step tutorials provide hands-on reinforcement for what you've learned.Maya at a Glance is the perfect introduction and reference to the Academy Award(r) winning Maya 3D animation and effects software.
Keywords: Computer animation,Maya (Computer file)